INNOVATIONS IN NUTRITION AS RISK-DECREASING FACTOR OF ALIMENTARY-DEPENDENT DISEASES IN INFANTS - T.V. Borodulina; N.E. Sannikova; L.N. Malyamova (Вопросы современной педиатрии)
The prevalence of breast feeding in Sverdlovsk region during last 5 years is analyzed. An adherence to breast feeding increases in presence of regional social support of pregnant and nursing women and provision with dry specialized milk mixture «Bellakt Mama». All artificially fed children 0–8 months old received adopted mixture «Bellakt 0–12», and children under 3 years old have opportunity (if they have social need) to receive liquid and past-like milk products for children’s nutrition, dry milk products for children after 1 year old and quick-dissolving cereals. Special attention is given to children’s nutrition in boarding schools. Rachitis, hypotrophy, functional intestinal disorders and other alimentary-dependent states are diagnosed 1.3 times frequently and anemia — 1.7 times frequently in children from orphans’ houses and boarding schools than in whole population. For the correction of micronutrient deficiency in infants, fortified milk drink «Be Healthy» («Bud Zdorov») was developed; it contains prophylactic doses of vitamins (A, D, E, C, PP) and microelements (iodine, iron, zinc, selenium).Key words: infants, health, nutrition, milk mixture(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (4): 111–114)